A Bibliometric Analysis of The Schizophrenia Publications of South East Asia in 2002-2023 - Nudhar, Lathifah; Syakurah, Rizma Adlia; Idris, Haerawati; Ramadhan, Muhammad Syahrul (Jurnal Ners, 2023)
Aims: We intend to do examine the productivity in literature related to schizophrenia in South East Asia trends in over 2 decades using bibliometric analysis. Method: We performed a systematic search through Web of Science Core Collection (WoSCC) database to searched articles related to schizophrenia between 1 January 2002 and 1 June 2023 and refined by Countries/Regions of 11 South East Asia countries. After filtering irrelevant publications, the VOSviewer later processed the informations and give visualizations of publications maps such as keywords, country, institutions, country, etc. Results: Of the total 876 literatures from Web of Science Core Database identified, 301 articles included in further analysis. There were increasing number of article related to schizophrenia published from 2002 to 2023. The analysis of selected keywords grouped them into six clusters according to similar topic. Analysis based on country revealed that Singapore published the most number of publications (41%) followed by Malaysia (29%) of total 301 articles. Analysis of authors showed that most of the top 10 authors were from Singapore with the highest paper was conducted by Chong SA with 50 total publications (16.6%). Conclusion: The research on schizophrenia mainly related to pharmacological treatment, psychosocial impact, comorbidities and pathophysiology. The research related to mental health policy and community based services stil need further explorations Keywords: Bibliometric, Schizophrenia, Publications